Performance analysis of ERS using R134a - An experimental investigation (Part 3) – Experimental results. Issue 1 (March 2021) - Kumar, Vikas; Tiwari, Sandeep; Sachdeva, Gulshan; Jain, Vaibhav
Abstract: The paper presents the experimental results of the ERS using R134a as a refrigerant. The performance analysis of the single-phase ejector is already analysed in the previous research paper of the series. Additionally, the design and dimension of the ERS is also calculated by the second research paper of the series. In this paper, the experimental results of the fabricated experimental setup are presented for various operating conditions.